Analysis of the Influence of Influencer Marketing and Content Quality on Purchasing Decisions for Skintific Skincare Products (A Case Study of Gen Z TikTok Shop Users in Pamekasan) - Sitti Afiyatun Najeh; Siti Masruroh (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study aims to examine and analyze the influence of influencer marketing and content quality on the purchasing decisions of Skintific skincare products among Generation Z TikTok Shop users in Pamekasan. The increasing use of TikTok as a dominant social media platform among Generation Z, along with the widespread promotion of skincare products through TikTok Shop, has created significant opportunities for interactive marketing. The researchers observed that the interactive marketing strategies implemented by Skintific through TikTok Shop features have a substantial impact on brand awareness and consumers' purchasing decisions in Pamekasan. Therefore, this study seeks to determine the effect of Skintific’s interactive marketing through TikTok Shop features on brand awareness and its impact on consumers’ purchasing decisions. This research employed a quantitative approach, with data collected through questionnaires distributed to Generation Z TikTok Shop users in Pamekasan. The sampling technique used was purposive sampling, involving 100 respondents. Data processing and analysis were conducted using IBM SPSS software. The results indicate that influencer marketing and content quality partially have a positive and significant effect on purchasing decisions. Furthermore, both variables simultaneously exert a significant influence on the purchasing decisions of Skintific skincare products. These findings suggest that the higher the credibility of influencers and the more attractive and informative the content presented, the greater the likelihood that consumers will make a purchase.